2020
DOI: 10.1002/ijc.33027
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of hepatitis B virus infection and viral DNA integration in non‐Hodgkin lymphoma

Abstract: Hepatitis B virus (HBV) infection has been reported to be associated with non‐Hodgkin lymphoma (NHL). However, the evidence is limited to the seroepidemiological study. There is a lack of evidence showing the HBV infection and integration in NHL cells. Here, we reported that in the Shanghai area, the positive rates of serum HBsAg (OR: 3.11; 95% CI: 2.20‐4.41) and HBeAg (OR: 3.99; 95% CI: 1.73‐9.91) were significantly higher in patients with NHL. HBsAg, HBcAg and HBV DNA were detected in 34.4%, 45.2% and 47.0% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…EGFLAM , a protein coding gene which plays a role in matrix assembly and cell adhesiveness was associated with higher risk of reporting moderate to severe xerostomia. It is considered a biomarker in some cancers including a hypomethylated tumor maker in ovarian cancer 53 and with altered expression in non-Hodgkin lymphoma 54 . Importantly, expression of this gene correlates with cell proliferation, migration, invasion, and poor prognosis by activating the P13/AKT pathway in Glioblastoma 55 .…”
Section: Discussionmentioning
confidence: 99%
“…EGFLAM , a protein coding gene which plays a role in matrix assembly and cell adhesiveness was associated with higher risk of reporting moderate to severe xerostomia. It is considered a biomarker in some cancers including a hypomethylated tumor maker in ovarian cancer 53 and with altered expression in non-Hodgkin lymphoma 54 . Importantly, expression of this gene correlates with cell proliferation, migration, invasion, and poor prognosis by activating the P13/AKT pathway in Glioblastoma 55 .…”
Section: Discussionmentioning
confidence: 99%
“…5,10 Especially in cases of ML, genetic evidence revealed HBV as a risk factor. 11,12 The main evidence was the integration of HBV DNA in lymphoid tissue. As a result, the role of HBV integration and oncogenesis had been considered as a promising treatment mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous studies, we found that HBV makers assay was different between DLBCL patients and general population. To date, previous studies have been focused on the association between HBsAg, HBV DNA and DLBCL development (20,24,28) and it's found that patients with positive HBsAg had higher risk of DLBCL. In fact, HBsAg-positive patients only account for less than 10% of total DLBCL patients and the progression of lymphoma has been reported to be correlated with host immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, HBV antigen was discovered in lymphoma tissue (20,21) and bone marrow cells from DLBCL patients (22). Besides, HBV DNA existed in peripheral blood mononuclear cells (23) and tumor tissue (20,21,24) from DLBCL patients. Besides, HBV had the ability to infect B lymphocytes in vitro (20) and then the integration of HBV DNA into the host genome was found in lymphoma (24), indicating the potential role of HBV infection in lymphoma development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation